PENGARUH BEBAN PAJAK TANGGUHAN, FREE CASH FLOW DAN PROFITABILITAS TERHADAP MANAJAMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE (2018-2021) - Aron, Aron Jordan Lekhenila; Timbul Hamonangan Simanjuntak; Carolina F. Sembiring (Buletin Ekonomi, 2024)
These studies aim to determining effects of deferred tax expense, Free Cashes Flow and Profitabilities on earnings managements in foods and beverages subsector manufacturing company list on Indonesia Stock Exchange on 2018-2021 periodic. Population in these studies were 30 company and samples of 11 company with periodic of 4 years. Sampling techniques using purposive sampling techniques. Methods use is descriptive analyst and panel data regressions analysis following by auto correlation test, heteroscedasticity test, multicollinearity test, and correlation analyst. Results of these studies indicate that simultaneously, variable of deferred tax expense, Free Cashes Flow, profitabilities have no significancy effects on earning managements. Partials test result showing that deferred tax expense, free cash flow, profitability has significancy negative effects on earning managements. Keywords: Deferred Tax Expense, Free Cashes Flow, Profitability and Profit Management